2017
DOI: 10.4172/2155-6156.1000726
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol can Replace Insulin in the Treatment of Type 2 Diabetes Mellitus

Abstract: Introduction: A large number of patients with diabetes mellitus do not want to take insulin or any injectable medication. Carvedilol can replace insulin in the treatment of T2 diabetes mellitus. Carvedilol alone or with oral anti-diabetic drugs (OAD) can replace the entire dose of insulin for patients with T2 diabetes (T2D). Carvedilol can replace insulin in patients on OAD who need insulin. Glycemic control was achieved in patients with T2D. This study was based on the hypothesis that carvedilol decreases ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In the current study, we used carvedilol, a third-generation beta-blocker agent with vasodilating action [35, 36] which can completely block the effects of excessive catecholamine, to investigate whether therapeutically targeting the adrenergic overdrive from chronic excess of basal norepinephrine in obesity could lead to metabolic benefits on the glucose metabolism. In agreement with the results from recent clinical studies [31, 33, 46], we found that carvedilol treatment during HFD-induced obesity improved glucose tolerance and insulin sensitivity possibly by suppressing the hepatic glucose overproduction and enhancing the muscular insulin signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we used carvedilol, a third-generation beta-blocker agent with vasodilating action [35, 36] which can completely block the effects of excessive catecholamine, to investigate whether therapeutically targeting the adrenergic overdrive from chronic excess of basal norepinephrine in obesity could lead to metabolic benefits on the glucose metabolism. In agreement with the results from recent clinical studies [31, 33, 46], we found that carvedilol treatment during HFD-induced obesity improved glucose tolerance and insulin sensitivity possibly by suppressing the hepatic glucose overproduction and enhancing the muscular insulin signaling pathway.…”
Section: Discussionsupporting
confidence: 92%
“…31 Also, carvedilol reduces insulin resistance by sensitizing insulin receptors, inhibiting the sympathetic nervous system, which is significant in insulin resistance. 32 According to previous studies, it can be said that carvedilol can be a suitable drug in the treatment of cardiovascular diseases in diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…Carvedilol (1) was found to reduce insulin resistance by increasing the sensitivity of insulin receptors (IRs) and by reducing the activity of the sympathetic nervous system [50]. The adrenergic system, in part through beta-2 adrenergic receptors, regulates glucose and lipid metabolism in the liver, adipose tissue, and skeletal muscle.…”
Section: Carvedilolmentioning
confidence: 99%